(untitled) (International Journal of Banking and Finance, 2023)
The long-term behaviour of stock markets are of significant importance to asset managers and financial experts due to its direct link with security price valuation. Volatility persistence has a significant impact on the returns of security prices due to its time varying properties. However, there is no real meaningful effect of current volatility on future security prices and returns if the volatility is transitory and not persistent. The aim of this study was to explore conditional volatility properties and determine whether the current volatile environment would persist in the JSE, S&P 500, Nasdaq Index, SSE, CAC 40 and DAX markets. Using a GARCH 1.1 model and a Markov switching model, the findings revealed that volatility would persist in the JSE, S&P 500, Nasdaq Index, SSE, CAC 40, and the DAX from their ARCH and GARCH coefficients, as well as the delay parameters. In addition, the effects of past volatility in the Nasdaq, CAC 40, and DAX would remain in the forecast of variance. A diversified and broader investment approach should be used in the JSE, S&P 500, Nasdaq Index, SSE, CAC 40, and DAX indexes to mitigate risk, and portfolio formation should not concentrate on any sector or asset classes.